Hexokinase2-engineered T cells display increased anti-tumor function - Zur, Raphaëlle Toledano; Zurinam, Shiran Didi; Radman, Maria; Funaro Balouka, Elia; Borodianskiy-Shteinberg, Tatiana; Saur, Dieter; Cohen, Cyrille J. (Frontiers in Immunology, 2025)
BackgroundT cells face significant metabolic challenges in the tumor microenvironment (TME), where cancer cells monopolize critical nutrients like glucose and amino acids. This metabolic competition supports tumor growth while impairing T-cell anti-tumor responses, partly by reducing glycolytic function. Hexokinase 2 (HK2), a key enzyme in glycolysis, plays a pivotal role in maintaining T-cell functionality.MethodsTo enhance T-cell function, primary human T cells were genetically engineered to overexpress HK2 alongside a tumor-specific receptor. These engineered T cells were tested in vitro and in vivo to evaluate their metabolic and therapeutic efficacy.ResultsHK2-engineered T cells exhibited increased glycolytic capacity, leading to enhanced cytokine secretion, activation marker expression, and metabolic activity compared to controls. In vivo studies using a human tumor xenograft model demonstrated the superior therapeutic efficacy of HK2-engineered T cells, including delayed tumor growth and improved survival.ConclusionHK2 overexpression improves T-cell metabolic fitness and functionality in hostile TMEs, offering a promising foundation for the development of next-generation immunotherapies targeting T-cell metabolism.